1994
DOI: 10.1093/ajcp/101.4.519
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Heat Shock Protein 70 Expression with Estrogen Receptor Levels in Invasive Human Breast Cancer

Abstract: The authors studied the role of 70-Kd heat shock protein (HSP70) in the progression of breast cancer by examining the correlation between the expression of HSP70 and epidermal growth factor receptor, c-erbB-2, p53, and estrogen receptor in 124 cases of invasive primary human breast cancers. Positivity of an anti-HSP70 monoclonal antibody, C92, was closely associated with the elevation of estrogen receptor (P < .008), whereas it inversely correlated with the expression of p53 (P < .01). In addition, the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 0 publications
1
26
0
4
Order By: Relevance
“…Abundant data have been published on the increased expression of HSP70 in several tumors, such as breast cancer (Takahashi et al 1994;Lazaris et al 1997;Vargas-Roig et al 1997), ovarian cancer (Elpek et al 2003), carcinoma of the uterine cervix (Kaur and Ralhan 1995;Park et al 1999), lung cancer (Zhong et al 2003), prostate cancer (Abe et al 2004;Cornford et al 2000), and other types of cancer (reviewed in Ciocca and Calderwood (2005)) . Colorectal tumors also exhibit increased HSP70 expression (Hwang et al 2003;Dundas et al 2005;Pfister et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Abundant data have been published on the increased expression of HSP70 in several tumors, such as breast cancer (Takahashi et al 1994;Lazaris et al 1997;Vargas-Roig et al 1997), ovarian cancer (Elpek et al 2003), carcinoma of the uterine cervix (Kaur and Ralhan 1995;Park et al 1999), lung cancer (Zhong et al 2003), prostate cancer (Abe et al 2004;Cornford et al 2000), and other types of cancer (reviewed in Ciocca and Calderwood (2005)) . Colorectal tumors also exhibit increased HSP70 expression (Hwang et al 2003;Dundas et al 2005;Pfister et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, HSP90 stabilizes Akt and oncogenic forms of mutant epidermal growth factor receptor, both of which contribute to the growth of a variety of cancers including gliomas (13)(14)(15). HSP70, in a complex with HSP90 and HSP40, also serves to regulate the function and turnover of the estrogen receptor, increasing its activation and driving estrogen-dependent cellular responses (16,17). HSP70 and HSP90 are also critically involved in the DNA-binding properties and stability of p53, and by stabilizing mutant p53, contribute to its role in transformation (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…A strict correlation between HSP70 levels and increased oestrogen receptors has also been detected [53]. Significant increases in HSP27 and HSP70 in its inducible form have also been observed in canine mammary tumour, particularly in the more invasive neoplastic cells, therefore these proteins (and HSP90) play a meaningful role in the multiple processes leading to malignant transformation and tumour progression in the canine mammary gland [12].…”
Section: Diagnostic and Prognostic Implications Of Hsp Expression In mentioning
confidence: 88%
“…Clinical-pathological studies have shown that the inducible form of the HSP70 family (HSP72) is associated with poor differentiation and the presence of mutated p53 in breast cancers [53], and its nuclear staining pattern has been reported to be correlated to tumour size [54]. A strict correlation between HSP70 levels and increased oestrogen receptors has also been detected [53].…”
Section: Diagnostic and Prognostic Implications Of Hsp Expression In mentioning
confidence: 99%